2015
DOI: 10.1371/journal.pone.0129366
|View full text |Cite
|
Sign up to set email alerts
|

Hypnotics and the Occurrence of Bone Fractures in Hospitalized Dementia Patients: A Matched Case-Control Study Using a National Inpatient Database

Abstract: BackgroundPreventing falls and bone fractures in hospital care is an important issue in geriatric medicine. Use of hypnotics is a potential risk factor for falls and bone fractures in older patients. However, data are lacking on the association between use of hypnotics and the occurrence of bone fracture.MethodsWe used a national inpatient database including 1,057 hospitals in Japan and included dementia patients aged 50 years or older who were hospitalized during a period of 12 months between April 2012 and M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
34
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 32 publications
2
34
0
1
Order By: Relevance
“…Falls may result in fractures, which delay recovery and lengthen hospitalisation. Occurrence of fractures in patients with dementia is associated with hypnotic medicines, specifically short‐acting benzodiazepine hypnotics, ultrashort‐acting nonbenzodiazepine hypnotics, hydroxyzine, risperidone, and perospirone . Both medical and surgical inpatients with dementia are at higher risk of 4 common complications, UTIs, PUs, pneumonia, and delirium, and medical patients are also at increased risk from sepsis and “failure to rescue” .…”
Section: Resultsmentioning
confidence: 99%
“…Falls may result in fractures, which delay recovery and lengthen hospitalisation. Occurrence of fractures in patients with dementia is associated with hypnotic medicines, specifically short‐acting benzodiazepine hypnotics, ultrashort‐acting nonbenzodiazepine hypnotics, hydroxyzine, risperidone, and perospirone . Both medical and surgical inpatients with dementia are at higher risk of 4 common complications, UTIs, PUs, pneumonia, and delirium, and medical patients are also at increased risk from sepsis and “failure to rescue” .…”
Section: Resultsmentioning
confidence: 99%
“…One study 6 showed that 97% of delirium patients suffered from sleep-awake cycle disturbance and attention disturbance. Further, delirium is a serious concern in the geriatric field because it causes many in-hospital accidents, including falls and fractures 56 . However, the results of a randomized controlled trial have shown that delirium is treatable with chronobiological therapies 57 58 , including ramelteon, a melatonin receptor agonist 57 .…”
Section: Discussionmentioning
confidence: 99%
“…However, few studies to date have examined how CNS‐active medications may affect fall risk in older adults with dementia, despite the fact that nearly 80% of community‐dwelling older adults with dementia have been prescribed a CNS‐active medication . The existing literature on CNS‐active medications and falls in older adults with dementia was largely conducted in institutional settings (e.g., nursing home or hospital) and found increased risk of falls or fractures associated with various classes of CNS‐active medications including antipsychotics, antidepressants, anxiolytics, and hypnotics . Another major gap in the existing literature is that most studies have focused on individual CNS‐active medication classes rather than combined exposures .…”
mentioning
confidence: 99%
“…The existing literature on CNS‐active medications and falls in older adults with dementia was largely conducted in institutional settings (e.g., nursing home or hospital) and found increased risk of falls or fractures associated with various classes of CNS‐active medications including antipsychotics, antidepressants, anxiolytics, and hypnotics . Another major gap in the existing literature is that most studies have focused on individual CNS‐active medication classes rather than combined exposures . This is an important gap given that polypharmacy of CNS‐active medications in older adults without dementia is associated with increased risk of falls, and it was estimated that more than half of community‐dwelling older adults with dementia have been prescribed a combination of CNS‐active medications .…”
mentioning
confidence: 99%
See 1 more Smart Citation